Conductive paste and conductive pattern using the same
By using a combination of silver-coated copper sheet and silver-coated silica powder in the conductive paste, the problem of insufficient line width deviation and migration resistance during the printing process of the conductive paste is solved, and high precision, low resistivity and excellent working performance are achieved effect.
Patent Information
- Application Number
- CN202180016102.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-11
- Filing Date
- 2021-02-16
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-02-16
AI Technical Summary
The existing conductive paste can easily lead to line width deviation and impregnation during the printing process, resulting in circuit short circuits and insufficient migration resistance.
A silver-coated copper sheet is used as the substrate, and silver-coated silica powder is added therein to form a conductive paste. The conductive paste may also contain a binder resin, a solvent, and a curing agent.
The circuit pattern printing is achieved with less line width deviation and high precision, which improves electrical conductivity and migration resistance, and has moderate viscosity and fluidity, which optimizes the workingability.
Smart Images

Figure CN115136257B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste for forming a conductive pattern such as an electrode of an electronic device, and a conductive pattern using the conductive paste. Background Art
[0002] Conductive paste is used in various applications, such as mounting and fixing semiconductor elements (semiconductor chips) such as ICs and LSIs on metal sheets called lead frames, forming circuits on substrates by printing, etc., or forming electrodes of electronic components such as capacitors.
[0003] In addition, with the increase in the integration of semiconductor chips and the high density of circuits on circuit substrates in recent years, conductive pastes are required to be able to print circuit patterns with little line width deviation and high precision, and also to have high electrical and thermal conductivity and high migration resistance in the printed circuit patterns, and to have excellent workability due to moderate viscosity and fluidity.
[0004] For example, in JP Patent Gazette No. 2012-18783 (Patent Document 1), the following conductive paste is disclosed: by adding silver microparticles with an average primary particle size of 10 nm to 200 nm to silver particles with an average particle size of 0.5 μm or more, the fluidity of the conductive paste is suppressed, thereby forming wiring of a conductive film with low volume resistivity, and improving the adhesion and printability with respect to the substrate.
[0005] In addition, JP-A-2019-102273 (Patent Document 2) discloses a conductive paste that suppresses viscosity reduction by using three types of fillers including nanoparticles in order to maintain low electrical resistance and have an appropriate viscosity for maintaining a thin line shape as much as possible.
[0006] However, in the conductive pastes described in Patent Documents 1 and 2, it is difficult to disperse the nano-sized filler, and thus the fluidity tends to be high. When the fluidity is too high, there is a problem that the conductive paste will penetrate after printing, causing deviation in the line width, which will cause a short circuit in the circuit. In addition, there is a problem that the conductive pattern formed using these conductive pastes may not have high migration resistance.
[0007] In addition, if the filling amount of conductive powder such as silver particles increases, it will be difficult to disperse. For this reason, the previous compositions highly filled with flaky (or flat) silver powder, spherical silver powder, etc. are prone to poor appearance, and also have problems such as reduced bonding strength and workability.
[0008] Prior Art Literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2012-18783
[0011] Patent Document 2: JP-A-2019-102273 Summary of the invention
[0012] Problem that the invention aims to solve
[0013] Therefore, the object of the present invention is to provide a conductive paste and a conductive pattern (circuit pattern) using the conductive paste, which can print the conductive pattern with a small line width deviation and high precision, and the printed conductive pattern also has high electrical conductivity and high migration resistance, and has excellent workability due to having moderate viscosity and fluidity.
[0014] Means for solving problems
[0015] In view of the above problems, the inventors have repeatedly conducted intensive studies on the types and shapes of conductive powders and the combinations of different conductive powders that are effective in suppressing the deviation of line width caused by impregnation during printing and the occurrence of migration and for achieving high electrical conductivity and excellent workability. As a result, they found that as a conductive paste, a silver-coated copper sheet (flake) is used as a base and silver-coated silica powder is added thereto, so that the above problems can be solved. As a result, the inventors have completed the present invention.
[0016] That is, according to the present invention, a conductive paste comprising a silver-coated copper sheet and a silver-coated silica powder and a conductive pattern using the conductive paste can be provided. In addition, the conductive paste of the present invention may further contain a binder resin, a solvent, and may contain a curing agent.
[0017] The conductive paste of the present invention is a composition formed into a paste by adding a silver-coated copper sheet and a silver-coated silica powder and adding a binder resin to them. As long as the silver-coated copper sheet, the silver-coated silica powder and the binder resin are included, other components such as a solvent and a defoaming agent may be included as needed within a range that does not impair the effects of the present invention.
[0018] The silver-coated copper flakes used in the present invention are not particularly limited as long as they are flaky copper powders coated with silver, and known materials can be used. The volume average particle size (D 50 ) is preferably 1.0 μm or more and 50 μm or less, and more preferably 2.0 μm or more and 20 μm or less. In particular, as long as the volume average particle size (D 50) is 2.0 μm or more and 20.0 μm or less, and it is very easy to deal with fine lines when drawing circuits. In addition, as copper powder coated with silver, spherical or substantially spherical copper powder, or sheet copper powder is known, but from the viewpoint of suppressing the reduction of electrical contacts after circuit formation and suppressing the increase of resistance, it is preferred to use silver-coated copper sheets in the present invention.
[0019] In addition, the silver-coated copper sheet can be completely covered with silver, or a portion of the copper can be exposed. The case where the silver is completely covered is suitable because the resistivity value will become smaller. The mixing amount of the silver-coated copper sheet is preferably 10 volume % or more and 40 volume % or less relative to the total non-volatile components of the conductive paste, and it is more preferred if it is 30 volume % or more and 40 volume % or less. As long as the mixing amount of the silver-coated copper sheet is 10 volume % or more and 40 volume % or less, the workability can be improved by having appropriate viscosity and fluidity while suppressing the resistivity value to a low level.
[0020] The silver-coated silica powder used in the present invention is not particularly limited as long as it is silica powder coated with silver, and a known material can be used. The volume average particle size (D 50 ) is preferably 0.050 μm or more and 50.0 μm or less, and more preferably 0.1 μm or more and 5.0 μm or less. In particular, as long as the volume average particle size (D 50 ) is 0.1 μm or more and 5.0 μm or less, the resistivity value can be suppressed low by achieving a high filling rate.
[0021] In addition, the silver-coated silica powder may be completely coated with silver or may have a portion of the silica exposed. The case where the silver is completely coated is suitable because the resistivity value becomes smaller. As for the mixing amount of the silver-coated silica powder, the volume ratio of the silver-coated copper sheet to the silver-coated silica powder is preferably in the range of 99:1 to 15:85, and more preferably in the range of 99:1 to 20:80.
[0022] As long as the volume ratio of the silver-coated copper sheet to the silver-coated silica powder is in the range of 99:1 to 15:85, the fluidity of the conductive paste obtained will be particularly suitable, the deviation of the line during printing will be reduced, and the electrical conductivity and migration resistance of the formed circuit pattern will also be improved. In addition, the shape of the silver-coated silica powder can be used without particular limitation as long as it is a particle. As long as it is in a particle shape, it is particularly suitable for use because of its excellent fluidity.
[0023] In addition, the numerical value (ratio) range expressed using "from" or "to" in the present specification indicates a range including the numerical values (ratios) described before and after "from" or "to" as the minimum value (ratio) and the maximum value (ratio), respectively.
[0024] The binder resin used in the present invention is not particularly limited, and known resins can be used. Examples of thermosetting resins include epoxy resins, phenolic resins, urea resins, unsaturated polyester resins, alkyd resins, polyurethanes, and thermosetting polyimides. In addition, thermoplastic resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyester, and polyamides having functional groups remaining at the ends may also be used together with a curing agent.
[0025] In order to achieve workability and printability suitable for various printing methods such as screen printing, the resin binder is preferably blended at a ratio of 30 volume % or more and 60 volume % or less relative to the total non-volatile components of the conductive paste.
[0026] The solvent used in the conductive paste of the present invention is not particularly limited. It can be appropriately selected according to the solubility of the resin used, the type of printing method, etc. Examples of the solvent of the present invention include ester solvents, ketone solvents, glycol ether solvents, aliphatic solvents, alicyclic solvents, aromatic solvents, alcohol solvents, water, etc., or a mixture of two or more thereof.
[0027] In addition, examples of ester solvents include ethyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, amyl acetate, ethyl lactate, dimethyl carbonate, etc. Examples of ketone solvents include acetone, methyl ethyl ketone, methyl isobutyl ketone benzene, diisobutyl ketone, diacetone alcohol, isophorone, cyclohexanone, etc. Examples of glycol ether solvents include acetates of monoethers such as ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, and ethylene glycol monobutyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, etc., and acetates of these monoethers.
[0028] On the other hand, examples of aliphatic solvents include n-heptane, n-hexane, isohexane, isoheptane, etc. Examples of alicyclic solvents include methylcyclohexane, ethylcyclohexane, cyclohexane, etc. Examples of aromatic solvents include toluene, xylene, tetralin, etc. Examples of alcohol solvents (except the above-mentioned glycol ether solvents) include ethanol, propanol, butanol, etc.
[0029] In addition, by using the above-mentioned conductive paste of the present invention to print multiple straight lines on a PET resin sheet with intervals of about 100 μm, the circuit pattern obtained in this way has a small deviation in line width, so adjacent lines will not short-circuit (contact) each other. In addition, a circuit pattern in which the electrical conductivity of each line is excellent can be obtained.
[0030] Effects of the Invention
[0031] The conductive paste of the present invention has excellent workability due to its moderate viscosity and moderate fluidity, and can achieve the excellent effect of being able to print circuit patterns with small line width deviation and high precision, and can also achieve the excellent effect of high electrical conductivity and high migration resistance in the printed conductive pattern. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a microscope photograph of a circuit pattern (conductive pattern) printed using the conductive paste of Example 4.
[0033] Figure 2 This is a microscope photograph of a circuit pattern (conductive pattern) printed using the conductive paste of Comparative Example 1.
[0034] Figure 3 This is a microscope photograph of a circuit pattern (conductive pattern) printed using the conductive paste of Comparative Example 3. DETAILED DESCRIPTION
[0035] A conductive paste and a conductive pattern using the conductive paste according to an embodiment of the present invention will be described in detail below with reference to the accompanying drawings. The present invention is not limited to the following embodiments, and various modifications can be made without departing from the technical concept of the present invention.
[0036] [Example]
[0037] 1. Preparation of conductive paste
[0038] The conductive paste according to one embodiment of the present invention and the conductive paste of the comparative example were prepared according to the following raw materials and conditions (see "Table 1").
[0039] [Example 1]
[0040] The following parts were prepared and then kneaded using a dispersant and a three-roll mixer to prepare the conductive paste of Example 1: As silver-coated copper sheets, 65.1 g of a volume average particle size (D 50 ) of TOYAL TecFiller (registered trademark) / TFM-C05F (manufactured by Toyo Aluminum Co., Ltd.) with a volume average particle size (D 50) was TOYAL TecFiller (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a particle size of 2 μm; as a binder resin, 12.0 g of Elitel (registered trademark) / UE-3210 (manufactured by UNITIKA Co., Ltd.) was prepared; as a curing agent, 1.7 g of blocked isocyanate (product name: 7992, manufactured by Baxenden Co., Ltd.) was prepared; and as a solvent, 24.9 g of a mixed solvent obtained by mixing ethyl carbitol acetate and isophorone in a weight ratio of 16:9 was prepared.
[0041] [Example 2]
[0042] As silver-coated silica powder, 0.57 g of a volume average particle size (D 50 The conductive paste of Example 2 was prepared under the same conditions as in Example 1 except that TOYALTecFiller (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a thickness of 2 μm.
[0043] [Example 3]
[0044] As silver-coated silica powder, 1.2 g of a volume average particle size (D 50 A conductive paste of Example 3 was prepared under the same conditions as in Example 1 except that TOYAL TecFiller (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a thickness of 2 μm.
[0045] [Example 4]
[0046] As silver-coated silica powder, 2.3 g of a volume average particle size (D 50 A conductive paste of Example 4 was prepared under the same conditions as in Example 1 except that TOYAL TecFiller (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a thickness of 2 μm.
[0047] [Example 5]
[0048] As a silver-coated copper sheet, 25.9 g of a volume average particle size (D 50 ) of TOYAL TecFiller (registered trademark) / TFM-C05F (manufactured by Toyo Aluminum Co., Ltd.) with a volume average particle size (D 50 A conductive paste of Example 5 was prepared under the same conditions as in Example 1 except that TOYAL TecFiller (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a thickness of 2 μm.
[0049] [Comparative Example 1]
[0050] A conductive paste of Comparative Example 1 was prepared under the same conditions as in Example 1 except that the silver-coated silica powder was not mixed.
[0051] [Comparative Example 2]
[0052] Instead of mixing the silver-coated copper sheet, 47.9 g of silver-coated silica powder with a volume average particle size (D 50 A conductive paste of Comparative Example 2 was prepared under the same conditions as in Example 1 except that TOYAL TecFiller (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a particle size of 2 μm.
[0053] [Comparative Example 3]
[0054] Instead of preparing the silver-coated copper sheet, 7.9 g of a volume average particle size (D 50 A conductive paste of Comparative Example 3 was prepared under the same conditions as in Example 1 except that TOYAL TecFiller (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a particle size of 2 μm.
[0055] [Comparative Example 4]
[0056] As a substitute for the silver-coated silica powder, 2.3 g of a volume average particle size (D 50 A conductive paste of Comparative Example 4 was prepared under the same conditions as in Example 1 except that spherical silver powder with a diameter of 5.7 μm (product name: HXR-Ag, manufactured by Nippon Atomize Processing Co., Ltd.) was used.
[0057] [Comparative Example 5]
[0058] As an alternative to the silver-coated copper sheet, 65.1 g of a volume average particle size (D 50 ) of 4.8 μm silver flakes (product name: TCG-1, manufactured by Tokuri Chemical Research Institute Co., Ltd.), as silver-coated silica powder, 2.3 g of volume average particle size (D 50 A conductive paste of Comparative Example 5 was prepared under the same conditions as in Example 1 except that TOYAL TecFiller (registered trademark) / TFM-S02P (manufactured by Toyo Aluminum Co., Ltd.) with a particle size of 2 μm.
[0059] [Comparative Example 6]
[0060] As a substitute for the silver-coated copper sheet, 65.1 g of a volume average particle size (D 50) was a 4.8 μm silver flake (product name: TCG-1, manufactured by Tokuri Chemical Research Institute Co., Ltd.), and the conductive paste of Comparative Example 6 was prepared under the same conditions as in Example 1, except that the silver-coated silica powder was not mixed.
[0061] Table 1 shows the amount (g) of each component added to the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6 and the blending ratio (Vol %) of each component to the total non-volatile content of the conductive pastes.
[0062]
Table 1
[0063]
[0064] 2. Production of circuit patterns (conductive patterns)
[0065] The conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6 were used to prepare a screen plate made of stainless steel, with a screen mesh number of 325, an emulsion thickness of 10 μm, a line width of 100 μm, and a circuit pattern with a spacing of 100 μm between each line. The screen plate was used to print on a PET resin sheet by a screen printer (product name: DP-320 type screen printer, manufactured by Newlong Precision Industry Co., Ltd.). Then, the sheet printed with the circuit pattern was dried at 150° C. for 30 minutes to prepare a circuit pattern for evaluation.
[0066] 3. Evaluation of conductive paste and circuit pattern
[0067] (1) Viscosity
[0068] To examine the relationship between the workability and impregnation of the conductive paste, the viscosity of the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6 was measured at 25° C. and 0.5 rpm using a B-type viscometer (model: DV2THBCJ0, manufactured by Brookfield).
[0069] (2) Line width deviation
[0070] The above-mentioned evaluation circuit pattern made using the conductive paste of Examples 1 to 5 and Comparative Examples 1 to 6 was observed at a magnification of 50 times using an inspection microscope (product name: ECLIPSE L200, manufactured by Nikon) and an image was taken. Next, the obtained image was binarized using image analysis software (product name: Winroof 2018, manufactured by Mitani Shoji Co., Ltd.). The line width of 1000 parts was measured from the binarized image, and the value of 3σ, which is an indicator of the deviation of the line width, was obtained. 3σ refers to an interval of 3 times the standard deviation (σ). As long as it is a normal distribution, about 99.7% of the samples will be within the range of ±3σ of the mean value.
[0071] The deviation of the line width of the circuit pattern is that the smaller the value of 3σ is, the more preferable it is. However, if the value of 3σ exceeds 50μm, it is evaluated as "×" (poor) because there is a possibility of short circuit between adjacent lines when power is turned on, etc., and the case below 50μm is evaluated as "○" (good). In addition, when a short circuit (contact) is observed in a part of adjacent lines from the beginning of the formation of the circuit pattern, it is evaluated as "×" (poor) regardless of the value of 3σ. Table 2 shows the above results.
[0072] In addition, among the above-mentioned evaluation circuit patterns, Figure 1 A microscope photograph of a circuit pattern produced using the conductive paste of Example 4 is shown. Figure 2 A microscope photograph of a circuit pattern produced using the conductive paste of Comparative Example 1 is shown, and Figure 3 A microscope photograph of a circuit pattern produced using the conductive paste of Comparative Example 3 is shown.
[0073] (3) Migration resistance
[0074] The migration resistance of the circuit pattern was evaluated by keeping each evaluation circuit pattern at 85°C, 85% humidity, and 50 V applied voltage, and measuring the time until short circuit occurred. The presence or absence of short circuit in the circuit pattern was confirmed using a migration tester (product name: MODEL MIG-87B, manufactured by IMV Co., Ltd.).
[0075] The migration resistance shows that the longer the time until the circuit pattern short-circuit occurs, the better the migration resistance is. In this embodiment, the time until the short-circuit occurs is 800 hours or more and is evaluated as "○" (good), and the time less than 800 hours is evaluated as "×" (bad). Table 2 shows the above results.
[0076] (4) Resistivity value
[0077] For the resistivity value (Ω·em) of the circuit pattern, a screen plate made of polyester resin, 280 meshes of screen, 9 microns of emulsion thickness and 4.8 cm×4.8 cm of quadrilateral shape is used to make the evaluation. The conductive paste is printed on the PET film using the evaluation screen plate, and dried at 150°C for 30 minutes to form a coating film for the product obtained in this way. In addition, the thickness of the coating film is confirmed by measuring with a digital caliper standard outside diameter micrometer (trade name: IP65COOLANTPROOFMicrometer, manufactured by Mitutoyo Co., Ltd.). It is confirmed by measuring with a 4-probe surface resistance measuring instrument (trade name: LorestaGP, manufactured by Mitsubishi Analytech Co., Ltd.). In each evaluation circuit pattern, any 5 points are measured, and the average value is taken as the resistivity value. Specifically, the size of the printed material, the average thickness of the printed material, and the coordinate data of the measuring points are input into the above-mentioned 4-probe surface resistance measuring device and the value obtained by automatic calculation is used as the resistivity value of the conductor layer (circuit pattern / conductive pattern).
[0078] The smaller the resistivity value, the better the conductivity. The so-called size of the printed material refers to the size consisting of the maximum length and the maximum width of the pattern of a given shape of the printed material. The smaller the resistivity value, the better. -4 The case with a value less than 2.0 × 10 -4 The case of Q·cm was evaluated as "×" (poor). Table 2 shows the above results.
[0079] Regarding the comprehensive evaluation of each evaluation circuit pattern, in the above-mentioned evaluations of "line width deviation", "migration resistance" and "resistivity value", in any case, only the case where "○" is obtained will be evaluated as "○" (good), and in each evaluation, even if there is 1 "×" case, it will be evaluated as "×" (poor) in the comprehensive evaluation.
[0080] Table 2 shows the evaluation results of the conductive pastes of Examples 1 to 5 and Comparative Examples 1 to 6 and the circuit patterns (conductive patterns) produced using the conductive pastes.
[0081]
Table 2
[0082]
[0083] 4. Investigation
[0084] According to Table 2, when the conductive pastes of Examples 1 to 5 and the conductive pastes of Comparative Examples 1 to 6 are compared, the conductive paste of the present invention can obtain good results in any of the evaluations of "line width deviation", "migration resistance" and "resistivity value" of the printed circuit pattern (conductive pattern) by using a silver-coated copper sheet as a base and adding silver-coated silica powder thereto. The results show that the conductive pattern can be printed with a small line width deviation and high precision, and the printed conductive pattern also has high electrical conductivity and thermal conductivity and high migration resistance, and has excellent workability by having a viscosity of 30 Pa·s or more and 70 Pa·s or less.
[0085] In particular, by comparing the conductive pastes of Examples 1 to 5 with the conductive pastes of Comparative Examples 1 to 3, it is found that if the volume ratio of the silver-coated copper sheet to the silver-coated silica powder is preferably in the range of 99:1 to 15:85, and more preferably in the range of 99:1 to 20:80, then in the printed circuit pattern, the line width deviation is small, and excellent migration resistance and conductivity can be obtained. Furthermore, if the volume ratio of the silver-coated copper sheet to the silver-coated silica powder is in the range of 99:1 to 90:10 as in the conductive pastes of Examples 1 to 4, even better migration resistance can be obtained.
[0086] In addition, regarding the conductive pastes of Examples 1 to 5, by setting the amount of the silver-coated copper flakes to be 10% by volume or more and 40% by volume or less relative to the total non-volatile components of the conductive paste, the deviation of the line width in the printed circuit pattern is small, and excellent migration resistance and conductivity can be obtained, and the resistivity value can be suppressed to a low level while having appropriate viscosity and fluidity to achieve improved workability. It was further determined that if the amount of the silver-coated copper flakes to be 30% by volume or more and 40% by volume or less relative to the total non-volatile components of the conductive paste as in the conductive pastes of Examples 1 to 4, more excellent migration resistance can be obtained.
[0087] Furthermore, it was found that in the conductive pastes of Examples 1 to 5, in order to achieve workability and printability suitable for various printing methods such as screen printing, it is effective to mix the resin binder at a ratio of 30 volume % or more and 60 volume % or less relative to the total nonvolatile components of the conductive paste.
[0088] Regarding the conductive pastes of Examples 1 to 5, it was found that when the volume average particle size (D 50 ) is preferably 1.0 μm or more and 50 μm or less, and more preferably 2.0 μm or more and 20 μm or less. Then, in the printed circuit pattern, the deviation of the line width is small, and it will be extremely easy to deal with fine lines when drawing the circuit pattern.
[0089] In addition, regarding the conductive pastes of Examples 1 to 5, it was found that when the volume average particle size (D 50 ) is preferably 0.050 μm or more and 50.0 μm or less, and more preferably 0.1 μm or more and 5.0 μm or less. By achieving a high filling rate, the resistivity value is suppressed to a low level and the deviation of the line width in the printed circuit pattern is also reduced.
[0090] In addition, according to Figures 1 to 3 It was found that, with respect to a circuit pattern (conductive pattern) obtained by printing a plurality of lines at intervals of approximately 100 μm using the conductive paste of the present invention, adjacent lines will not short-circuit (contact) each other due to small deviation in line width, and further, a circuit pattern in which each line has excellent electrical conductivity can be obtained.
[0091] Description of Reference Numerals
[0092] L···Printing line
[0093] G···Gap (PET resin sheet)
[0094] S···Short circuit part (contact part)
Claims
1. A conductive paste, characterized in that: Contains silver-coated copper sheets and silver-coated silica powder, The mixing ratio of the silver-coated copper sheet to the silver-coated silica powder is in the range of 99:1 to 38.4:4.3 by volume. The average particle size of the silver-coated copper sheet is 2.0 μm or more and 20.0 μm or less, and the average particle size of the silver-coated silica powder is 0.1 μm or more and 5.0 μm or less, The amount of the silver-coated copper sheet blended is 10% by volume or more and 40% by volume or less relative to the total non-volatile components of the conductive paste.
2. The conductive paste according to claim 1, characterized in that: The conductive paste further contains a resin binder in an amount of 30% by volume or more and 60% by volume or less based on the total nonvolatile components of the conductive paste.
3. A conductive pattern, characterized in that: The conductive paste according to claim 1 or 2 is used for forming the conductive paste.
Citation Information
Patent Citations
Conductive paste
JP2012018783A
Conductive paste composition
JP2019102273A
Conductive paste and conductive pattern
JP2012079457A
Conductive resin composition and semiconductor device
JP2015026519A